Strategi Pembinaan Ibadah melalui Kegiatan Mabit (Malam Bina Iman dan Taqwa) di Sekolah Islam Terpadu - Rosmaimuna Siregar; Darliana Sormin; Jumaita Nopriani Lubis; Sina Asriani Dongoran (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
This study aims to explore the implementation of the Malam Bina Iman dan Taqwa (Mabit) program at the Integrated Islamic Junior High School (SMA IT) as part of students' religious practice development. This research adopts a qualitative approach with a descriptive method. The research informants include the school principal, supervising teachers, and students participating in the Mabit program. Data were collected through in-depth interviews, observations, and document analysis. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The findings show that the Mabit activities at SMA IT are systematically designed to foster students' worship practices. The core activities include congregational prayers, Islamic studies, muhasabah (self-reflection), and habituation of sunnah worship such as tahajjud, qobliyah and ba'diyah prayers, Qur'an recitation, and are integrated with the Gerakan Subuh Berjama'ah (GSB, or Collective Dawn Prayer Movement). The program is supported by the active participation of supervising teachers and intensive oversight from the school foundation to ensure maximum student engagement and involvement. Mabit offers an experiential learning opportunity that leaves a lasting impression on students' religious development. It enhances worship awareness, as well as students' understanding and practice of religious duties.